2021
DOI: 10.3389/fonc.2021.649778
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA KCNMB2-AS1 Promotes SMAD5 by Targeting miR-3194-3p to Induce Bladder Cancer Progression

Abstract: PurposeBladder cancer is a common malignant tumor of the urinary system, with the fourth-highest incidence of male malignant tumors in Europe and the United States. So far, the mechanism of bladder cancer progression and metastasis has not been clarified. The aim of our study was to validate the way of long noncoding RNA (lncRNA) KCNMB2-AS1 on the metabolism and growth of bladder cancer cells by miR-3194-3p/SMAD5.Patients and MethodsThe Gene Expression was analyzed by qRT-PCR in bladder cancer tissues and cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Transwell assay demonstrated that sh-KCNMB2-AS1 repressed both the migration and invasion of ESCA cells compared with sh-NC ( Figure 1(g,h) ). Since tumor cell stemness is believed to be the cause tumor recurrence and metastasis, the prevention of tumor cell stemness can hinder the development of the tumor to a certain degree [ 41 ]. Then, we investigated the influence of KCNMB2-AS1 on cell stemness in ESCA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transwell assay demonstrated that sh-KCNMB2-AS1 repressed both the migration and invasion of ESCA cells compared with sh-NC ( Figure 1(g,h) ). Since tumor cell stemness is believed to be the cause tumor recurrence and metastasis, the prevention of tumor cell stemness can hinder the development of the tumor to a certain degree [ 41 ]. Then, we investigated the influence of KCNMB2-AS1 on cell stemness in ESCA.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, KCNMB2-AS1 knockdown inhibited ESCA cell growth and motion, and KCNMB2-AS1 overexpression promoted ESCA cell growth and motion, suggesting an oncogenic role of KCNMB2-AS1 in ESCA. In addition, tumor cell stemness is believed to be the cause tumor recurrence and metastasis, and the prevention of tumor cell stemness can hinder the development of the tumor to a certain degree [ 41 ]. Several lncRNAs such as FMR1 antisense RNA 1 (FMR1-AS1) [ 47 ], small nucleolar RNA host gene 12 (SNHG12) [ 48 ], HLA complex P5 (HCP5) [ 49 ], fer-1 like family member 4 (pseudogene) (FER1L4) [ 50 ] were reported to regulate ESCA cell stemness.…”
Section: Discussionmentioning
confidence: 99%
“…SMAD5 is closely related to the occurrence and progression of various cancers. Chen et al [ 40 ] reported that SMAD5 was highly expressed in bladder cancer. We found that SMAD5 was highly expressed in HCC, suggesting that SMAD5 might play a positive role in the progression of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…In cancer biology, miRNAs are implicated in a variety of malignancies by modulating different downstream targets [ 40–43 ]. In BC cells, miRNAs are involved in the regulation of cell proliferation, migration, and invasion, self-renewal, angiogenesis, as well as the development of resistance [ 44–48 ]. In our results, we further revealed that circLONP2 could bind to miR-584-5p and inhibit its function.…”
Section: Discussionmentioning
confidence: 99%